Effect of water release behavior by pH-sensitive microgels on hydration, microstructure of cementitious materials - Gengtong Zhang; Huiyun Xia; Dongwei Cao; Huaxin Chen; Weihua Li (Case Studies in Construction Materials)
Superabsorbent polymer (SAP) has been effectively applied in cement-based materials for controllable water release to alleviate autogenous shrinkage. In this paper, a type of pH-sensitive microgel was synthesized and its water release rate in two simplified stages was investigated. To explore the water evolution and hydration characteristics of cement paste, free water content, chemical bound water and hydration heat are quantified by vacuum freeze-drying, thermogravimetry and isothermal calorimetry methods. The effects of extra water and microgel on the properties and microstructure of cement-based materials were also studied. The water absorption process of microgel in cement filtrate is slow and stable without early desorption, and the retention capability of microgel reduced the evaporation of free water. As the humidity dropped, the stored water is driven by a humidity gradient and drained almost entirely within 7 days. The addition of extra water and pH-sensitive microgel increased the total water cement ratio, thus promoting the further full hydration of cement. This is also the main factor leading to a decrease in compressive strength. Also, microgel refined the microstructure of mortar. A layer of hydration products formed around each curing area can be attributed to the slow water release of microgel.